2003
DOI: 10.1007/s00421-002-0729-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of pre-exercise ingestion of trehalose, galactose and glucose on subsequent metabolism and cycling performance

Abstract: The glycaemic and insulinaemic responses to different carbohydrates vary and these have been suggested to affect performance. The purpose of the present study was to determine the effects of pre-exercise ingestion of glucose (GLU), galactose (GAL) and trehalose (TRE) on metabolic responses at rest and during exercise and on subsequent time-trial (TT) performance. Eight well-trained male cyclists completed three exercise trials separated by at least 3 days. At 45 min before the start of exercise subjects consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 26 publications
4
54
3
2
Order By: Relevance
“…These findings are in agreement with previous studies reporting no differences in whole body substrate utilization during exercise at 65% VO 2peak , after pre-exercise consumption of glucose, galactose or trehalose [46] or galactose, glucose and fructose combinations [47]. It is therefore likely that the continuous intake of the drinks throughout the exercise period, or the moderate intensity of the exercise protocol, resulted in a reduction in glucose requirements as the main fuel substrate.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with previous studies reporting no differences in whole body substrate utilization during exercise at 65% VO 2peak , after pre-exercise consumption of glucose, galactose or trehalose [46] or galactose, glucose and fructose combinations [47]. It is therefore likely that the continuous intake of the drinks throughout the exercise period, or the moderate intensity of the exercise protocol, resulted in a reduction in glucose requirements as the main fuel substrate.…”
Section: Discussionsupporting
confidence: 93%
“…Although, Dumortier et al (28) reported that when a meal of 550 kcal 路 路 路 路 路 路 (57% CHO, 26% protein, and 17% fat) was consumed 1 h or 3 h before exercise by diabetes patients, fat oxidation was higher after 3 h compared with 1 h during exercise. Moreover, the amount of carbohydrate intake in the present study was 2.4 g/kg body mass, which was higher than in previous studies (approximately 1.0-2.2 g/kg body mass) (4,5,7,8). The meal form was also in contrast to many previous studies in which beverages or simple foods were used.…”
Section: Discussioncontrasting
confidence: 86%
“…Fats are supplied by meals, and also by adipose tissues, but CHO must be acquired from meals before exercise because little is stored as glycogen in the liver or muscle tissue. Previous studies have been conducted on the ergogenic effects of CHO feeding before exercise (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). It was reported that CHO solution (such as glucose and maltodextrin) feeding before exercise can improve exercise performance through enhanced endurance exercise capacity (2,4,5,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One employed a 20-min warm up at 65% maximal oxygen uptake (VO 2max ) followed by a self-paced time trial (TT) of B40 min (Jentjens and Jeukendrup, 2003). No effect of galactose ingestion on performance was apparent.…”
Section: Introductionmentioning
confidence: 99%